Perceived psychological well being and emotional competence in medium level wrestlers - Juan González Hernández (Federación Extremeña de Balonmano; University of Extremadura, 2011)
Abstract Sportsmen who practise martial arts indicate, to general way, that practical this one produces effects psicosociales different (and major) to the produced ones for other physical activities. Though all the sports can promote the psychological well-being, the processes and effects are not the same in martial arts and in other types of physical activities. Nevertheless, not always the findings of the investigations have joined with the programs of intervention. The ways of life and the opportunities of health, well-being and development of the young persons have a very narrow relation with the sociocultural context, facilitating or preventing this traffic towards the adult age. The context is a factor intervener and determinant in the behavior for what it turns out suitable bear in mind the environments perceived by the subject (Figueroa et al., 2005). In this respect, and in spite of the fact that nowadays the emotional intelligence is one of the topics of major study and interest inside the Psychology, this one is an aspect to make concrete inside the methodologies of training, both formative and competitive. One presents here a descriptive and transverse study in the one that has told himself with a sample of sports young women (N=45), that they practise different modalities of combative sports (karate and judo) of the city of Murcia. The results suggest us that, so much the promotion of sports environments for the practice of martial arts as a sports activity organized, it influences positively in the perception of the psychological well-being, which benefits the development of the autoconcept and cognitive development of the same ones.  Key words: psychological well-being, emotional intelligence, combative sports, indicators of performance